2011
DOI: 10.1080/03235408.2010.505366
|View full text |Cite
|
Sign up to set email alerts
|

Survey report on occurrence of root knot disease in winged bean

Abstract: Winged bean (Psophocarpus tetragonolobus) is of rapidly increasing interest as a high-protein multipurpose crop; in the future the winged bean could become as important as the soybean in world agriculture, with the added bonus of yielding substantial quantities of edible, high-protein root tubers. During the survey of root-knot nematodes (Meloidogyne species) on vegetable crops in Uttar Pradesh (India), it was observed that winged bean was restricted to home gardens and backyard cultivation where it was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Паразитують різні види галових нематод і на рослинах цукрового буряку [51,52]. Встановлено, що M. incognita шкодить посівам буряків в Греції [53], M. halpa -в Киргизстані [54], США [55] та колишній Югославії [56], а M. naasi -в Нідерландах [57], Бельгії [58] та Польщі [53].…”
Section: результати дослідженняunclassified
“…Паразитують різні види галових нематод і на рослинах цукрового буряку [51,52]. Встановлено, що M. incognita шкодить посівам буряків в Греції [53], M. halpa -в Киргизстані [54], США [55] та колишній Югославії [56], а M. naasi -в Нідерландах [57], Бельгії [58] та Польщі [53].…”
Section: результати дослідженняunclassified
“…Around the world, including India, the yields of vegetable crops are comparatively lower due to abiotic and biotic constraints. Vegetable fields that are heavily infested with plant-parasitic nematodes have been reported with 80% loss (Anamika et al, 2011). Many biotic constraints, including plant-parasitic nematodes, limit the profitable production of vegetables qualitatively and quantitatively (Khan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…But no detailed study for the nematode infestation has been reported except some sporadic findings. Vegetable fields that are heavily infested with plant-parasitic nematodes have been reported with 80% loss (Anamika et al, 2011). Plant-parasitic nematodes (PPNs) are one of the major limiting factors in the crop production and cause severe yield losses worldwide (Asif et al, 2018;Khan et al, 2019;Ghareeb et al, 2020).…”
Section: Introductionmentioning
confidence: 99%